2016
DOI: 10.1016/j.wneu.2016.08.053
|View full text |Cite
|
Sign up to set email alerts
|

Higher Mean Arterial Pressure Values Correlate with Neurologic Improvement in Patients with Initially Complete Spinal Cord Injuries

Abstract: Background Traumatic spinal cord injury (SCI) guidelines recommend to maintain mean arterial pressures (MAPs) above 85 mmHg for 7d following SCI to minimize spinal cord ischemia. Some doubt that patients with initially complete injuries benefit. Objective To assess the relationship between MAP augmentation and neurological improvement in SCI patients stratified by initial AIS score. Methods High-frequency MAP values of acute SCI patients admitted over a six-year period were recorded and values were correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 35 publications
1
46
0
1
Order By: Relevance
“…This analysis is similar to one we recently performed to examine the relationship between mean arterial blood pressure values and outcome from spinal cord injury. 6,12…”
Section: Data Curationmentioning
confidence: 99%
“…This analysis is similar to one we recently performed to examine the relationship between mean arterial blood pressure values and outcome from spinal cord injury. 6,12…”
Section: Data Curationmentioning
confidence: 99%
“…20,31 Nine studies were retrospective reviews that collected information on MAP after SCI as well as neurological outcome measures throughout the postinjury period. 6,9,16,17,19,21,27,33 Levi et al 20 performed a prospective study in which the authors described the outcomes of a group of 50 patients who underwent spinal immobilization or fixation as indicated, with their postinjury care at a trauma center between 1990 and 1991. An MAP goal higher than 90 mm Hg was maintained with fluids and dopamine for the 1st week after injury, although some patients required the addition of dobutamine for additional support.…”
Section: Relationship Of Map Goals To Outcomesmentioning
confidence: 99%
“…More recently, results show that patients with complete SCI may derive greater benefit from MAP augmentation. 14 The timing of intervention, and the duration for which MAP values are below threshold, may additionally influence neurological outcome. Similarly, a systematic review by Sabit et al of the effect of MAP on functional outcome revealed that achieving normotension is the most effective treatment for the patient with SCI.…”
Section: Spinal Cord Perfusion and Vasopressor Supportmentioning
confidence: 99%